Strategi Konten Marketing pada Media Sosial Instagram sebagai Strategi Pemasaran Digital Sate Taichan Senayan - Maulana Sanderson Pasaribu; Netti Nurlenawati; Dexi Triadinda (Journal of Management and Bussines (JOMB), 2024)
This research aims to identify and analyze the content marketing strategies implemented by Sate Taichan Senayan in facing intense competition on the Instagram platform. The research method uses a qualitative approach by collecting primary data through interviews and direct observation of the owner of Sate Taichan Senayan, while secondary data is obtained from journals, articles and library studies. Content analysis is used as the main framework to explore the content marketing strategy implemented by the company. The research results revealed that Sate Taichan Senayan adopted an approach based on the four stages of the customer journey: attention, interest, desire and action. In conclusion, provides in-depth insight into how culinary companies manage their content to achieve marketing effectiveness in the digital era, especially on visual platforms such as Instagram. Keywords: Content Marketing, Social Media, Digital Marketing